Urgensi Insya’ dalam Meningkatkan Maharatul Kitabah: Telaah atas Kompetensi Insya’ Mahasiswa STAI Nurul Iman Prodi Pendidikan Bahasa Arab Parung Bogor - Ismail , Abi; Isyanto, Nur; Ikhwan, Subaiki (STAINI Press, 2024)
Researchers found from several papers that the majority of students are students who are not graduates from Islamic boarding schools, so they have difficulty writing Arabic when teachers dictate the material. This difficulty is caused by the inability of students to write Arabic letters properly and correctly, which is caused by a lack of recognition of Arabic letters from the beginning, lack of practice, and low ability and willingness to learn Arabic, especially in Kitabah (writing) skills. This study aims to examine the urgency of Insya' in improving Maharatul Kitabah of PBA STAI Nurul Iman students. Data collection was carried out through observation techniques, in-depth interviews, and documentation. Data analysis uses Miles and Huberman's interactive analysis method, which includes data reduction, data presentation, and conclusion drawn. The methods applied in Insya' learning to improve Maharatul Kitabah include Thariqat Al-Ibtidaiyyah to start, Thariqat Al-Thattawwur to develop, Thariqat Al-Istiqrai to pour out the main ideas, and the Recording Method. Factors supporting Insya's urgency include: brilliant ideas, new innovations, writing discipline, and the habit of repeating (Muraja'ah). On the other hand, inhibiting factors include: laziness to look for new ideas and innovations, laziness to write, and lack of discipline in writing. The results of the study show that the urgency of Insya' is an important method to increase Maharatul Kitabah. In the Insya' method, students are taught about the rules of Arabic and how to structure sentences according to these rules. In addition, this method not only improves writing skills, but also encourages students to pour their thoughts, ideas, and innovations into writing essays in Arabic. This research still has limitations and needs further development. It is hoped that the results of this research can be a source of insight for readers in improving the quality of learning in their respective schools. Constructive criticism and suggestions from various parties are highly expected to improve this research. Keywords: Urgency Insya, Maharatul Kitabah, PBA Students